A cuo modified bismuth calcium niobate textured ceramic material and a method of manufacture
Patent Information
- Application Number
- CN202611131517.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-23
AI Technical Summary
然而,虽然压电性能得到了大幅提升,CBN基陶瓷却难以实现商业化应用,究其原因,目前的研究主要集中在压电性能的提升上,忽视了CBN基陶瓷在服役条件下性能动态稳定性这一根本性问题,导致CBN基陶瓷尚不能实现在高低温循环的长时服役要求
[0030]1. 现有技术中,纯CaBi2Nb2O9陶瓷在高温长时服役下,其铁电畴壁极易发生非本征热激发运动,导致压电性能剧烈波动甚至退极化。本发明通过在Na/Sm共掺杂的基体中精准引入适量的CuO,实现了A位与B位掺杂的强协同效应。Na/Sm共掺杂引起的局部晶格畸变显著降低了Cu离子在晶格中的掺杂形成能,使得Cu2+更易于取代B位的Nb5+。Cu2+的受主掺杂不仅诱导产生了氧空位以维持电荷平衡,更由于Cu2+自身强烈的Jahn-Teller效应,与氧空位结合形成了高度局域化的缺陷增强型Jahn-Teller畸变,即高浓度的强缺陷偶极子
。在高达650℃的极端温度下,这些深能级缺陷偶极子构筑了致密且强效的钉扎网络,死死锁住铁电畴壁,极大地抑制了畴壁的非本征不可逆位移。由此,本发明成功将室温至650℃范围内的压电系数d33变化率从21.08%骤降至4.96%以下,实现了压电温度稳定性的跨越式提升。
Smart Images

Figure CN122958175A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic material preparation technology, specifically relating to a CuO-modified bismuth niobate calcium-based textured ceramic material and its preparation method. Background Technology
[0002] Accelerometers (also known as accelerometers) are sensors that can collect the vibration acceleration of a measured object. Piezoelectric accelerometers, in particular, possess advantages such as excellent dynamic response and linearity, wide bandwidth, high sensitivity, large temperature range, simple structure, and stable performance, making them widely used in various fields and currently the mainstream vibration sensor. Piezoelectric vibration sensors designed for high-temperature environments have significant strategic value and are primarily used in critical areas related to national defense security, such as nuclear power units and aircraft wings. They are also specialized sensors used in the vibration state measurement of aero-engine health management systems, playing a vital role in the flight safety of aircraft.
[0003] As the core component of high-temperature piezoelectric vibration sensors, the performance of high-temperature piezoelectric materials directly determines key performance parameters such as operating temperature, sensing sensitivity, and temperature stability. Among various high-temperature piezoelectric materials, bismuth-calcium niobate (CaBi₂Nb₂O₉, CBN)-based ceramics possess an ultra-high Curie temperature (Ti). C With advantages such as high temperature resistance (~940 ℃), excellent insulation properties, and aging resistance, CBN-based ceramics have extremely high application potential in the field of high-temperature piezoelectric vibration sensors. However, addressing the issue of their extremely low piezoelectric properties, over the past two decades, efforts have been made to improve the piezoelectric coefficient of CBN-based ceramics. 33 The increase in piezoelectric coefficient from around 5 pC / N to over 30 pC / N has significantly improved the sensitivity of piezoelectric vibration sensors. However, despite the substantial improvement in piezoelectric performance, CBN-based ceramics have struggled to achieve commercial application. The reason for this is that current research primarily focuses on enhancing piezoelectric performance, neglecting the fundamental issue of the dynamic stability of CBN-based ceramics under service conditions. This results in CBN-based ceramics not yet meeting the requirements for long-term service under high and low temperature cycling. Existing research mainly focuses on increasing the room-temperature piezoelectric coefficient, failing to address the critical problem of drastic performance degradation under high-temperature, long-term service. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the first objective of this invention is to provide a method for preparing CuO-modified bismuth niobate calcium-based textured ceramic materials.
[0005] A second objective of this invention is to provide a CuO-modified bismuth niobate calcium-based textured ceramic material prepared by the above-described method. The bismuth niobate calcium-based textured ceramic material provided by this invention possesses high Curie temperature, high voltage response, and excellent high-temperature service stability.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] This invention discloses a method for preparing CuO-modified bismuth calcium niobate-based textured ceramic material. The method involves ball milling bismuth calcium niobate-based ceramic powder, CuO powder, solvent, and dispersant to obtain a mixed powder. A plasticizer and binder are added to the mixed powder, and the mixture is ball-milled to obtain a mixed slurry. Template grains are then added to the mixed slurry, and the mixture is ball-milled to obtain a ceramic slurry. The ceramic slurry is then cast on a casting machine to obtain a film. The films are stacked to obtain a green body. The green body undergoes a first pressing, debinding, and a second pressing to obtain a pressed compact. Finally, the pressed compact is sintered to obtain the bismuth calcium niobate-based textured ceramic material.
[0008] During the casting process, the doctor blade height is first set to 10-50 μm, preferably 10-15 μm, for the first casting. After casting, the film is dried to obtain the first layer of ceramic green film. Then, the doctor blade height is set to 5-50 μm higher than the first layer of ceramic green film, preferably 5-15 μm, for the second casting. After casting, the film is dried to obtain the second layer of ceramic green film. The above operation is repeated until a film with a total thickness of 200-500 μm, preferably 200-300 μm, is obtained.
[0009] In a preferred embodiment, bismuth niobate calcium-based ceramic powder, CuO powder, solvent, and dispersant are ball-milled for 18-36 hours to obtain a mixture. Plasticizer and binder are added to the mixture and ball-milled a second time to obtain a slurry. Template grains are then added to the slurry and ball-milled a third time to obtain a ceramic slurry.
[0010] The first ball milling speed is 150-250 rpm, and the first ball milling time is 18-36 hours;
[0011] The second ball milling speed is 150-250 rpm, and the second ball milling time is 12-36 hours;
[0012] The third ball milling operation is performed at a speed of 150-250 rpm for a duration of 0.5-12 h.
[0013] In this invention, bismuth calcium niobate-based ceramic powder is first ball-milled with CuO powder, solvent, and dispersant to uniformly disperse the CuO powder and partially dissolve it into the bismuth calcium niobate-based lattice, thus achieving element doping. Then, it is mixed with plasticizer and binder and ball-milled to ensure thorough and uniform mixing. Finally, template grains are introduced using a low ball-milling speed to ensure the integrity of the template structure while ensuring thorough and uniform mixing.
[0014] In a preferred embodiment, the chemical formula of the bismuth niobate calcium-based ceramic powder is Ca. 0.95 Na 0.025Sm 0.025 Bi2Nb2O9.
[0015] In a preferred embodiment, the amount of CuO powder added is 0.05 wt% - 0.2 wt% of the mass of the bismuth calcium niobate-based ceramic powder. In this invention, the amount of CuO powder added needs to be effectively controlled; excessive addition will lead to a deterioration in the ceramic's insulation performance.
[0016] In a preferred embodiment, the solvent is a mixed solution of xylene and anhydrous ethanol, wherein the volume ratio of xylene to anhydrous ethanol is 2-3:2.
[0017] In a preferred embodiment, the solid-liquid mass-volume ratio of the bismuth niobate calcium-based ceramic powder to the solvent is 50 g: 30-50 ml.
[0018] In a preferred embodiment, the dispersant is triethyl phosphate, and the solid-liquid mass-volume ratio of the bismuth niobate calcium-based ceramic powder to the dispersant is 50 g: 0.1-0.5 ml.
[0019] In a preferred embodiment, the plasticizer is composed of polyethylene glycol and dibutyl phthalate, the solid-liquid mass-volume ratio of the bismuth calcium niobate ceramic powder to polyethylene glycol is 50 g: 4-10 ml, and the solid-liquid mass-volume ratio of the bismuth calcium niobate ceramic powder to dibutyl phthalate is 50 g: 1-4 ml.
[0020] In a preferred embodiment, the binder is polyvinyl butyral, and the mass ratio of the bismuth niobate calcium-based ceramic powder to polyvinyl butyral is 50:2-5.
[0021] In a preferred embodiment, the doped calcium bismuth niobate ceramic template grains are plate-like, and their chemical formula is: Ca 0.95 Na 0.025 Sm 0.025 Bi2Nb2O9.
[0022] In a preferred embodiment, the amount of bismuth calcium niobate ceramic template grains added to the ceramic slurry is 3-8% of the mass of the bismuth calcium niobate ceramic powder.
[0023] In a preferred embodiment, the membrane sheets are stacked and then vacuum dried to obtain a green body. The drying temperature is controlled at 30-100℃ and the internal pressure at 20-70 kPa. Vacuum drying removes air bubbles from the green body.
[0024] In a preferred embodiment, the pressure of the first pressing is 100-500 MPa, and the pressing time is 10-30 minutes. In actual operation, the green blank is placed in a cold isostatic press for pressing to make the green blank dense.
[0025] In a preferred embodiment, the pressure of the second pressing is 100-500 MPa, and the time for the second pressing is 10-30 min.
[0026] In a preferred embodiment, the sintering process is as follows: the pressed blank is heated from room temperature to 1100-1200℃ at a heating rate of 1-10℃ / min and held at that temperature for 18-24 hours.
[0027] The sintering process of this invention, through long-term sintering and heat preservation, ensures highly oriented grains and improves texture.
[0028] The present invention also provides a CuO-modified bismuth niobate calcium-based textured ceramic material prepared by the above preparation method.
[0029] Beneficial effects:
[0030] 1. In existing technologies, pure CaBi₂Nb₂O₉ ceramics, under high-temperature and long-term service, are prone to endogeneous thermally excited motion of their ferroelectric domain walls, leading to drastic fluctuations in piezoelectric properties and even depolarization. This invention achieves a strong synergistic effect between A-site and B-site doping by precisely introducing an appropriate amount of CuO into a Na / Sm co-doped matrix. The local lattice distortion caused by Na / Sm co-doping significantly reduces the doping formation energy of Cu ions in the lattice, making Cu… 2+ Nb is more likely to replace B position 5+ Cu 2+ Acceptor doping not only induced the generation of oxygen vacancies To maintain charge balance, and more so because of Cu 2+ The strong Jahn-Teller effect, combined with oxygen vacancies, forms a highly localized defect-enhanced Jahn-Teller distortion, i.e., a high concentration of strong defect dipoles. At extreme temperatures up to 650°C, these deep-level defect dipoles construct a dense and powerful pinning network, tightly locking the ferroelectric domain walls and greatly suppressing their intriguing irreversible displacement. Thus, this invention successfully achieves piezoelectric coefficient dp in the range of room temperature to 650°C. 33 The rate of change plummeted from 21.08% to below 4.96%, achieving a leapfrog improvement in piezoelectric temperature stability.
[0031] 2. This invention ingeniously combines non-aqueous tape casting technology with a CuO micro-liquid phase mechanism: Under extremely narrow blade gaps, the shear force of the tape casting forces anisotropic sheet templates to undergo intense physical flipping and achieve highly consistent orientation. Simultaneously, trace amounts of CuO generate nanoscale micro-liquid phases in situ at the interface between the template and the matrix powder during the initial stage of high-temperature sintering. This micro-liquid phase acts as a perfect interfacial lubricant and mass transfer highway, enabling the highly oriented template to smoothly and stress-free absorb matrix particles for homogeneous epitaxial growth. This synergistic effect of mechanical confinement and chemical lubrication completely eliminates interfacial microcracks that are prone to occur during thick sheet stacking sintering, ultimately significantly improving the texture of the ceramic.
[0032] 3. This invention creatively matches an ultra-high temperature long-time sintering process of 18-24 hours at 1100-1200℃ to the unique lattice distortion environment and the large grain characteristics generated by highly textured Na / Sm co-doped systems. This demanding thermodynamic condition not only ensures sufficient lubrication of the interfacial micro-liquid phase but also provides ample diffusion driving force and atomic migration time, enabling Cu ions to completely traverse the large textured grains of tens of micrometers, achieving a uniform distribution throughout the bulk phase from grain boundaries to grain cores. This uniform diffusion at the lattice level depth completely eliminates the defect concentration gradient within the giant grains, constructing a continuous, dead-angle-free bulk phase throughout the entire piezoelectric ceramic. The defect dipole global pinning network perfectly ensures the material's ultra-high temperature stability at an extreme high temperature of 650℃, with a piezoelectric change rate as low as 4.96%.
[0033] 4. Benefiting from the dual coupling of the high orientation degree of template growth and the long-range ordered arrangement of defect dipoles along a specific crystallographic direction, the spontaneous polarization intensity is maximized within the ab plane. The ceramic material prepared by this invention maintains an ultra-high Curie temperature of 957.1℃ - 958.1℃ while exhibiting a high room-temperature piezoelectric coefficient da. 33 Maintaining a dielectric constant of 26.9-27.4 pC / N, and with a high-temperature dielectric loss of less than 0.03 at 600°C, this invention completely solves the global challenge of traditional high-temperature piezoelectric materials failing to simultaneously achieve high Curie temperature, high voltage response, and excellent high-temperature service stability. It provides an ideal material basis for piezoelectric vibration sensors in extreme environments such as aero-engine health management systems. Attached Figure Description
[0034] Figure 1 Schematic diagram of the casting process.
[0035] Figure 2 SEM image of the calcium bismuth niobate-based textured ceramic material obtained in Example 1.
[0036] Figure 3The dielectric temperature spectrum and corresponding Curie temperature T of the bismuth niobate calcium-based textured ceramic material obtained in Example 1 c .
[0037] Figure 4 In-situ temperature variation d of the bismuth niobate calcium-based textured ceramic material obtained in Example 1 33 Test image.
[0038] Figure 5 SEM image of the calcium bismuth niobate-based textured ceramic material obtained in Example 2.
[0039] Figure 6 The dielectric temperature spectrum and corresponding Curie temperature T of the bismuth niobate calcium-based textured ceramic material obtained in Example 2 c .
[0040] Figure 7 In-situ temperature variation d of the bismuth niobate calcium-based textured ceramic material obtained in Example 2 33 test.
[0041] Figure 8 SEM image of the calcium bismuth niobate-based textured ceramic material obtained in Comparative Example 1.
[0042] Figure 9 The dielectric temperature spectrum and corresponding Curie temperature T of the bismuth niobate calcium-based textured ceramic material obtained in Comparative Example 1 c .
[0043] Figure 10 In-situ temperature variation d of the bismuth niobate calcium-based textured ceramic material obtained in Comparative Example 1 33 Test image.
[0044] Figure 11 XRD patterns of ceramics obtained in Examples 1-2 and Comparative Examples 1-2 and their corresponding texture degrees.
[0045] Figure 12 SEM image of the calcium bismuth niobate-based textured ceramic material obtained in Comparative Example 2.
[0046] Figure 13 The PE and IE hysteresis loops of the bismuth-calcium based textured ceramic material obtained in Comparative Example 2. Detailed Implementation
[0047] Example 1:
[0048] Adding 0.1 wt% CuO yields textured CBNNS+CuO-0.1 wt% ceramic. Preparation steps:
[0049] 1. Ca 0.95 Na 0.025 Sm 0.025 Preparation of Bi2Nb2O9 template grains:
[0050] Weigh out the raw materials CaCO3 powder, Na2CO3 powder, Sm2O3 powder, Bi2O3 powder and Nb2O5 powder according to the stoichiometric ratio, and select the neutral salt NaCl-KCl (the molar ratio of NaCl and KCl is 1:1). The mass ratio of raw materials to neutral salt is 1:1.
[0051] The raw materials, neutral salt, zirconium balls, and anhydrous ethanol were placed in a ball mill jar at a mass ratio of 1:1.5:0.65 and ball milled at 300 r / min for 24 h, then dried and sieved.
[0052] The dried powder was poured into a crucible and kept at 1050℃ for 6 hours, with a heating rate of 5℃ / min.
[0053] The synthesized sample was washed with deionized water until the conductivity of the washing water dropped to 3 μS / cm, thus obtaining the desired powder.
[0054] 2. Ca 0.95 Na 0.025 Sm 0.025 Preparation of Bi2Nb2O9 ceramic matrix powder:
[0055] Preparation of Ca 1-2x Sm x Na x Bi2Nb2O9, Sm and Na doped modified bismuth calcium niobate ceramic with x = 0.025, is abbreviated as CBNNS-0.025.
[0056] Analytical purity CaCO3 powder, Na2CO3 powder, Sm2O3 powder, Bi2O3 powder and Nb2O5 powder were weighed according to stoichiometric ratio, and prepared according to the traditional solid-state method. Then, the raw materials were mixed with anhydrous ethanol, ball-milled at 300 r / min for 8 hours, pre-calcined at 925℃ for 2 hours, ball-milled again at 300 r / min for 12 hours, and dried to obtain ceramic matrix powder.
[0057] 3. Prepare the slurry
[0058] The composition of the ceramic slurry is shown in Table 1. First, an appropriate amount of ceramic matrix powder (composition: CBNNS-0.025) was weighed, and an appropriate amount of xylene / anhydrous ethanol was added as a solvent and triethyl phosphate as a dispersant. CuO powder was then added, and the mixture was ball-milled for 24 h. After ball milling, plasticizers (polyethylene glycol and dibutyl phthalate) and binders (polyvinyl butyral) were added, and ball milling continued for 24 h. Then, an appropriate amount (5 wt% of the ceramic matrix powder mass) of template grains was added, and the mixture was ball-milled for 6 h.
[0059] Table 1 Composition of Casting Slurry
[0060]
[0061] 4. Casting
[0062] The casting process is shown in the figure. First, the prepared slurry is slowly stirred under vacuum to remove air bubbles. Then, the treated ceramic slurry is poured into the casting machine, the doctor blade height is set to 10 μm, and casting is performed. After casting, it is dried to obtain the first layer of ceramic green film. Then, the doctor blade height is set to 20 μm, and casting is performed on the first layer of ceramic green film. After drying, the second layer of ceramic green film is obtained. Casting is repeated at 10 μm intervals up to 200 μm, and the above operation is repeated to obtain the final ceramic film.
[0063] 5. Cutting and stacking
[0064] Cut the scraped ceramic film into 30×30mm squares and stack them to a height of 20mm. Then, place the stacked green bodies into a vacuum drying oven and vacuum dry them at a temperature of 70℃ and an internal pressure of 45 kPa to remove air bubbles from the green bodies.
[0065] 6. Debinding and densification
[0066] The green compact is placed in a cold isostatic press, and the pressure is set to 300 MPa and maintained for 20 minutes to further densify the green compact. Then it is placed in a muffle furnace to remove the binder. After the binder is removed, it is cold isostatically pressed again under the same pressure.
[0067] 7. Sintering
[0068] The densified ceramic green body was placed in a muffle furnace and heated from room temperature to 1150℃ at a rate of 5℃ / min for 20 hours to obtain ceramic.
[0069] The bismuth-calcium-based textured ceramic material prepared in Example 1 has highly oriented grains, a texture degree f of 95.5%, a Curie temperature of 958.1℃, and a room-temperature piezoelectric coefficient d. 33 It reached 27.4 pC / N, with a piezoelectric coefficient d33 change rate of 4.96% from room temperature to 650℃ in real time, and a dielectric loss of only 0.028 at 600℃.
[0070] Example 2:
[0071] Other conditions were the same as in Example 1, except that 0.2 wt% CuO was added to obtain a textured CBNNS+CuO-0.2wt% ceramic with a texture degree f of 94.7%, a Curie temperature of 957.1℃, and a room temperature piezoelectric coefficient d. 33It reached 26.9 pC / N, with a piezoelectric coefficient d33 change rate of 7.66% from room temperature to 650℃ in real time, and a dielectric loss of only 0.019 at 600℃.
[0072] Comparative Example 1
[0073] Other conditions were the same as in Example 1, with CuO content of 0 wt% added, resulting in a textured CBNNS+CuO-0 wt% ceramic with a texture degree f of 85.6%, a Curie temperature of 946.1℃, a room temperature piezoelectric coefficient d33 of 31.1 pC / N, a real-time temperature change rate of 21.08% from room temperature to 650℃, and a dielectric loss close to 0.15 at 600℃.
[0074] Comparative Example 2
[0075] Adding 0.3 wt% CuO yielded a textured CBNNS+CuO-0.3 wt% ceramic. Testing the PE and IE hysteresis loops revealed excessive leakage current in the ceramic, indicating that excessive CuO addition caused a deterioration in the ceramic's insulation performance.
Claims
1. A method for preparing a CuO-modified bismuth niobate calcium-based textured ceramic material, characterized in that: Bismuth calcium niobate-based ceramic powder, CuO powder, solvent, and dispersant are ball-milled to obtain a mixed powder. Plasticizer and binder are added to the mixed powder and ball-milled to obtain a mixed slurry. Template grains are then added to the mixed slurry and ball-milled to obtain a ceramic slurry. The ceramic slurry is then cast on a casting machine to obtain a film. The films are stacked to obtain a green body. The green body is then subjected to a first pressing, debinding, and a second pressing to obtain a pressed green body. Finally, the pressed green body is sintered to obtain the bismuth calcium niobate-based textured ceramic material. During the casting process, the doctor blade height is first set to 10-50 μm for the first casting. After casting, the film is dried to obtain the first layer of ceramic green film. Then, the doctor blade height is set to 5-50 μm higher than the first layer of ceramic green film for the second casting. After casting, the film is dried to obtain the second layer of ceramic green film. The above operation is repeated until a film with a total thickness of 200-500 μm is obtained.
2. The method for preparing a CuO-modified bismuth niobate calcium-based textured ceramic material according to claim 1, characterized in that: Bismuth niobate calcium-based ceramic powder, CuO powder, solvent, and dispersant are ball-milled for 18-36 hours to obtain a mixture. Plasticizer and binder are added to the mixture and ball-milled a second time to obtain a slurry. Template grains are added to the slurry and ball-milled a third time to obtain a ceramic slurry. The first ball milling speed is 150-250 rpm, and the first ball milling time is 18-36 hours; The second ball milling speed is 150-250 rpm, and the second ball milling time is 12-36 hours; The third ball milling operation is performed at a speed of 150-250 rpm for a duration of 0.5-12 h.
3. The method for preparing a CuO-modified bismuth niobate calcium-based textured ceramic material according to claim 1 or 2, characterized in that: The chemical formula of the bismuth niobate calcium-based ceramic powder is Ca. 0.95 Na 0.025 Sm 0.025 Bi2Nb2O9.
4. The method for preparing a CuO-modified bismuth niobate calcium-based textured ceramic material according to claim 1 or 2, characterized in that: The amount of CuO powder added is 0.05 wt% - 0.2 wt% of the mass of the bismuth niobate calcium-based ceramic powder.
5. A method for preparing a CuO-modified bismuth niobate calcium-based textured ceramic material according to claim 1 or 2, characterized in that: The solvent is a mixed solution of xylene and anhydrous ethanol, wherein the volume ratio of xylene to anhydrous ethanol is 2-3:2; The solid-liquid mass-volume ratio of the bismuth niobate calcium-based ceramic powder to the solvent is 50 g: 30-50 ml; The dispersant is triethyl phosphate, and the solid-liquid mass-volume ratio of the bismuth niobate calcium-based ceramic powder to the dispersant is 50g:0.1-0.5ml.
6. A method for preparing a CuO-modified bismuth niobate calcium-based textured ceramic material according to claim 1 or 2, characterized in that: The plasticizer is composed of polyethylene glycol and dibutyl phthalate, the solid-liquid mass-volume ratio of the bismuth calcium niobate ceramic powder to polyethylene glycol is 50 g: 4-10 ml, and the solid-liquid mass-volume ratio of the bismuth calcium niobate ceramic powder to dibutyl phthalate is 50 g: 1-4 ml. The binder is polyvinyl butyral, and the mass ratio of the bismuth niobate calcium-based ceramic powder to polyvinyl butyral is 50:2-5.
7. A method for preparing a CuO-modified bismuth niobate calcium-based textured ceramic material according to claim 1 or 2, characterized in that: The template grains are plate-shaped and have the chemical formula: Ca 0.95 Na 0.025 Sm 0.025 Bi2Nb2O9; In the ceramic slurry, the amount of template grains added is 3 to 8% of the mass of the bismuth calcium niobate ceramic powder.
8. The method for preparing a CuO-modified bismuth niobate calcium-based textured ceramic material according to claim 1, characterized in that: The membranes are stacked and then vacuum dried to obtain a green body. The drying temperature is controlled at 30-100℃ and the internal pressure is 20-70 kPa. The pressure of the first pressing is 100-500 MPa, and the time of the first pressing is 10-30 min; The pressure for the second pressing is 100-500 MPa, and the pressing time is 10-30 minutes.
9. The method for preparing a CuO-modified bismuth niobate calcium-based textured ceramic material according to claim 1, characterized in that: The sintering process is as follows: the pressed blank is heated from room temperature to 1100-1200℃ at a heating rate of 1-10℃ / min and held for 18-24 hours.
10. A CuO-modified bismuth niobate calcium-based textured ceramic material prepared by the preparation method according to any one of claims 1-9.
